2012
DOI: 10.5402/2012/627596
|View full text |Cite
|
Sign up to set email alerts
|

The Tousled-Like Kinases as Guardians of Genome Integrity

Abstract: The Tousled-like kinases (TLKs) function in processes of chromatin assembly, including replication, transcription, repair, and chromosome segregation. TLKs interact specifically (and phosphorylate) with the chromatin assembly factor Asf1, a histone H3-H4 chaperone, histone H3 itself at Ser10, and also Rad9, a key protein involved in DNA repair and cell cycle signaling following DNA damage. These interactions are believed to be responsible for the action of TLKs in double-stranded break repair and radioprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 91 publications
(157 reference statements)
1
36
0
Order By: Relevance
“…40 As a kinase, TLK functions by phosphorylating its target proteins, such as the chromatin assembly factor ASF1 and Rad9. 40 In the Drosophila loss-of-function tlk mutant, nuclear divisions are arrested at interphase, and cells eventually undergo apoptosis. 34 Therefore, loss-of-function tlk should reduce cell numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 As a kinase, TLK functions by phosphorylating its target proteins, such as the chromatin assembly factor ASF1 and Rad9. 40 In the Drosophila loss-of-function tlk mutant, nuclear divisions are arrested at interphase, and cells eventually undergo apoptosis. 34 Therefore, loss-of-function tlk should reduce cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…40 In Drosophila, TLK phosphorylates ASF1 and causes nuclear division arrest and pupal lethality. 34 Our result showed that asf1 RNAi had no effect on the TLK-induced cell death Figure 4E), suggesting that the function of TLK on cell death was likely different from its role in chromatin organization.…”
Section: Figure 2 (Continued)mentioning
confidence: 99%
“…Another possibility is that the absence of this interaction may be a result of fundamental differences between budding yeast and mammalian cells in the mechanism of DNA damage checkpoint regulation. However, Asf1 has been shown to participate in nucleosome deposition following repair (Mello et al 2002) and interact with tousled-like kinases (TLKs), a family of kinases specific to metazoans that plays an extensive role in the regulation of replication, transcription, and repair (Groth et al 2003(Groth et al , 2005Mousson et al 2007;De Benedetti 2012). These observations implicate Asf1 with regulation of the DNA damage checkpoint in mammalian cells as well.…”
Section: Asf1 Facilitates Rad53 Dephosphorylationmentioning
confidence: 95%
“…There is a curve inflection following the second dose of doxo for both groups (+/-THD), and considering that the dose and schedule of doxo administration was not fully optimized, we concluded that perhaps a more quantitative model (MDA-231-Luc cells) to more precisely measure tumor growth could yield more definitive results. In any case, the tumors were excised at the end of the experiment (before the control group tumors reached the preset end point of 1,500 mm 3 ) and processed for immunohistochemistry (IHC) analysis. The mice were dosed on the last day before euthanasia with doxo to induce bona fide DSBs.…”
Section: Animal Studiesmentioning
confidence: 99%
“…3 Two TLK genes (TLK1 and TLK2) with several splice variants were identified in humans. TLK1/1B interacts specifically with the chromatin assembly factor Asf1 and Rad9, [4][5][6] and we have presented evidence that TLK1B promotes repair by processing the double-strand break (DSB) ends and disassembling chromatin nearby to facilitate the recruitment of repair proteins.…”
Section: Introductionmentioning
confidence: 99%